2020
DOI: 10.1097/coc.0000000000000789
|View full text |Cite
|
Sign up to set email alerts
|

Second-line Chemotherapy Prolongs Survival in Real World Patients With Advanced Biliary Tract and Gallbladder Cancers

Abstract: Background: Limited evidence is available regarding the survival benefit of second-line therapy in real world patients with advanced biliary tract and gallbladder cancer. Until very recently, there was a lack of randomized clinical trials to address this important question. In this multicenter population-based cohort study, the authors evaluated whether second-line therapy improves the survival of real world patients with advanced biliary tract and gallbladder cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…As with findings on disease progression, 2 L OS results from our analyses are consistent with those reported in the literature. Although the median OS of 11 months reported by Lowery et al 13 and median OS of 17 months reported in a recent multicenter, population‐based cohort study by Zaidi et al 18 are somewhat longer than the 6.6 to 7.7‐month median OS reported by others and nearly 2 to 3 times the 5.2‐month median OS of our study, our finding is in line with other studies. 7 , 8 , 9 , 10 , 14 , 16 , 17 Recent findings presented for the ABC‐06 trial describe a median OS of 6.2 months (95% CI, 5.4–7.6 months) from the start of 2 L treatment in patients treated with ASC + FOLFOX.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As with findings on disease progression, 2 L OS results from our analyses are consistent with those reported in the literature. Although the median OS of 11 months reported by Lowery et al 13 and median OS of 17 months reported in a recent multicenter, population‐based cohort study by Zaidi et al 18 are somewhat longer than the 6.6 to 7.7‐month median OS reported by others and nearly 2 to 3 times the 5.2‐month median OS of our study, our finding is in line with other studies. 7 , 8 , 9 , 10 , 14 , 16 , 17 Recent findings presented for the ABC‐06 trial describe a median OS of 6.2 months (95% CI, 5.4–7.6 months) from the start of 2 L treatment in patients treated with ASC + FOLFOX.…”
Section: Discussionsupporting
confidence: 90%
“…Existing studies report findings outside of the US, report data only from academic centers, include only older populations, or use older data. 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Therefore, with its large cohort of patients treated in the community oncology setting, our study aimed to provide real‐world insight into the rapidly evolving and growing 2 L treatment landscape for advanced or metastatic BTC.…”
Section: Introductionmentioning
confidence: 99%
“…GemCis/GemOx as CT1 and FOLFOX as CT2 have been established for patients with ABTC. [12] , [13] , [14] , [15] , 29 The survival times reported here are comparable to the OS of 9.5-11.7 months after CT1 11 , 13 , 14 and 6.7-7.2 months after CT2 [30] , [31] , [32] obtained in previous studies. In our analysis, OS was significantly dependent on the number of received therapy lines.…”
Section: Discussionsupporting
confidence: 87%
“…The combined chemotherapy regimens have been found to increase the overall survival of patients in clinical trials , but still, they have been found to have toxic effects, and resistance is developed later[ 3 , 71 , 72 ]. Whenever clinical trials were performed some unforeseen hurdles were found, including the side effects and development of resistance to a particular drug.…”
Section: Discussionmentioning
confidence: 99%